Interpretasi Bawah Permukaan dan Delineasi Struktur Cekungan Muna-Buton Berdasarkan Data Gravitasi Satelit - Muhammad Nur Ahsan Zakir; Wawan Gunawan Abdul Kadir; Eko Januari Wahyudi (Jurnal Rekayasa Geofisika Indonesia, 2023)
Island of Buton is a region located in the Southeast Sulawesi region, Indonesia. The formation of Buton Island is the result of intense tectonic processes, resulting in diverse geological resources, including natural resources such as oil and natural gas accumulated in a sedimentary basin. Gravity field measurements have been conducted to interpret subsurface structures in the Muna-Buton Basin. The data used consist of free air gravity anomaly data, requiring corrections for Bouguer and terrain to obtain a complete Bouguer anomaly. Anomaly separation is performed using trend surface analysis method. Gradient analysis is conducted on residual anomalies to delineate basin structures in the research area using several methods, including horizontal gradient, total gradient, tilt-angle horizontal gradient, and improved logistic filter. Qualitatively, two sub-basins can be delineated: Sub-basin A is in the east and sub-basin B is in the west. Sub-basin A is estimated to be the Bulu sub-basin, while sub-basin B is the Buton Strait sub-basin. Based on subsurface modeling results, there is a basement layer indicated to be at an estimated shallowest depth of 2 km in the Buton Strait sub-basin and an estimated shallowest depth of 3 km in the Bulu Basin sub-basin. The depth of this basement layer increases towards the center of the basin, reaching more than 4 km.